Avaliação do ciclo de vida (ACV) dos concretos compostos com agregados graúdos de construção e demolição em diferentes teores de substituição - Tonon, Danielli Cecim da Silva (2020)
The present study was developed with the purpose of performing a Life Cycle Assessment (LCA), evaluating the influence of using the Construction and Demolition Waste (CDW) as Recycled Concrete Aggregate (ARC) at different levels of substitution by natural aggregate. The damage mitigation caused by construction and demolition waste (CDW) has proven to be an excellent alternative in reducing the environmental impact caused by extraction activity of natural resources in order to satisfy the needs of the construction industry. One way to contribute in this reduction is incorporating these residues in the production of concretes. Those will be produced with 0%, 25%, 50%, 75% and 100% basalt replacement by CDW using Portland cement of high initial strength (CPV) and a sensitivity analysis will be performed in two different scenarios with different transport distances. The aim of this research is to perform the life cycle evaluation of concrete produced with RCD and to compare them with conventional concrete.